Preliminary results on novel adjuvant combinations suggest enhanced immunogenicity of whole inactivated pandemic influenza vaccines - Peletta, Allegra; Marmy, Aurélie; Guzelj, Samo; Ramos Barros, Alcidia; Jakopin, Žiga; Borchard, Gerrit (Frontiers in Drug Delivery, 2024)
Due to the inherent risk for a next pandemic influenza outbreak, there is a need and growing interest for the investigation of combinations of prophylactic vaccines and novel adjuvants, in particular to achieve antigen dose sparing and improved immunogenicity. Influenza is a virus with a high variability, where the specific vaccine target is constantly changing and represents a major challenge in influenza vaccine development. Currently, commercial inactivated influenza vaccines have a poor CD8+ T response which impacts cross-reactivity and duration of response. Adjuvanted influenza vaccines can increase immune responses thereby improve achieving better protection and cross-reactivity to help contain the spread of disease. An early exploration of a hybrid cholesterol-PLGA nanoparticle delivery system containing the saponin tomatine and a NOD2 (nucleotide-binding oligomerization domain 2) agonist called SG101 was conducted. This combination was preliminarily evaluated for its ability to induce cellular immunity when combined with whole inactivated virus (WIV) influenza vaccine. After manufacturing of the adjuvants using a single emulsion process, two formulations with different drug loading were selected and physico-chemically characterized, showing sizes between 224 ± 32 and 309 ± 45 nm and different morphologies. After ensuring lack of in vitro toxicity and hemolytic activity, the hybrid nanoparticle formulation was evaluated for its ability to induce humoral and cellular immunity when combined with whole inactivated virus (WIV) H5N1 influenza vaccine by intramuscular administration in mice, in a pilot in vivo assay. Hemagglutinin inhibition (HAI) titers for adjuvanted groups showed no significant difference compared to the group vaccinated with the antigen alone. Similarly, for CD4 + and CD8 + T cell responses, although the high drug loading formulation induced higher titers of IFNγ positive CD8 + T cells. These proof-of-concept results are encouraging to continue further investigations to develop the hybrid formulation with increased or different loading ratios, investigate manufacturing optimization and to evaluate the role of the individual immunostimulatory compounds on the immune responses.